Public procurement as a tool of ecological safety in civil aviation (ground maintenance) - Водоласкова, Катерина Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Problem setting.The development of the aviation industry is one of the significant indicators of state economic and technological development. However, this progress has side effects such as negative impact on environment. The main ecological problems in civil aviation are: aircraft noise; effects of emissions of exhaust gases of aircraft engines; various local problems, which arise due to the vicinity of airports, aviation-technical base, aircraft repair plants and other aviation companies. Analysis of resent research and publications.The issue of developing ways to improve the environmental and economic activities, including in the aviation industry, as well as various aspects of public procurement are studied by such domestic and foreign scientists, as Yu.Z.Drachuk, G.M Franchuk, L.V.Malakhov, H.O.Bilyavskyy, V.Ya.Shevchuk, S.S.Hrebionkin, M.Shreyers, K.Shaberh, K.Yakob, M.N.Postorino, J.Davenport, S.Erkmana, M.Chertova, I.L.Borodin, Yu.I.Pivovar, V.V.Smyrychynskiy, K.Jaehrling, H.O.Finnestrand, H.Torvatn, E.K.Sarter, D.Sack, D.Kauffmann, S.Kühn, L.B.Sherman and others. Article’s main body. Today environmental standards and regulations may be perceived as a brake for aviation development. However, this paradigm has to be changed and further improvement of aviation technologies in ground handling should be in progress synchronously with environmental safety with the observance of a high level balance between these two vectors. Objects of civil aviation ground handling are strategic state facilities that are used, in particular, to fulfill state’s functions. Therefore, the issue of airport activity financing also should be one of the priorities of the state. In this situation, public procurement can and has be used as a tool for environmental safety in aviation during ground handling and, potentially, be a stimulus for greening the whole industry. Examples of practical procurement system functioning as a way to protect the environment in many airports can be observed in various countries, which can be studied and adopted for domestic usage. Conclusion and prospects for the development. Due to ecological problems in the world the paradigm of the scientific community opinion concerning developing of new methods of environmental-economic regulation and control of enterprises economic activity is changing. The system of public procurement is not only a way for providing necessary goods, works and services, but also plays a key role in the efficient use of resources of the economy and, with purposeful and effective usage, can and have to be one of many tools to ensure environmental safety in ground handling of civil aviation.